La liberté dérivationnelle en ancien français - Marádi, Krisztina (Verbum – Analecta Neolatina, 2003)
In this study, the author provides a survey on a lexical aspect of Old French, namely the liberty of derivation with the prefixes entre-, mal- and mes-. The study presents the semantic components of these prefixes as well as a related morphological analysis. At the end of the paper, the author offers a possible explanation for the frequency of these prefixed forms.